Cover Feature: A Guanidyl‐Based Bivalent Peptidomimetic Inhibits K‐Ras Prenylation and Association with c‐Raf (Chem. Eur. J. 59/2019). Issue 59 (4th September 2019) - Tsubamoto, Mai; Le, Toan Khanh; Li, Minghua; Watanabe, Taku; Matsumi, Chiemi; Parvatkar, Prakash; Fujii, Hiroshi; Kato, Nobuo; Sun, Jiazhi; Ohkanda, Junko
Abstract : Hook to a hole : A cell‐permeable bivalent inhibitor of protein prenyltransferases binds to the active pocket and delivers a small module compound onto an interface of protein–protein interactions with K‐Ras, allowing inhibition of posttranslational lipid modification of K‐Ras and association with its downstream effector. More information can be found in the Full Paper by J. Ohkanda et al. on page 13531 .